Structural basis of HypK regulating N-terminal acetylation by the NatA complex - Weyer, Felix Alexander; Gumiero, Andrea; Lapouge, Karine; Bange, Gert; Kopp, Jürgen; Sinning, Irmgard (Nature Communications, 2017)
In eukaryotes, N-terminal acetylation is one of the most common protein modifications involved in a wide range of biological processes. Most N-acetyltransferase complexes (NATs) act co-translationally, with the heterodimeric NatA complex modifying the majority of substrate proteins. Here we show that the Huntingtin yeast two-hybrid protein K (HypK) binds tightly to the NatA complex comprising the auxiliary subunit Naa15 and the catalytic subunit Naa10. The crystal structures of NatA bound to HypK or to a N-terminal deletion variant of HypK were determined without or with a bi-substrate analogue, respectively. The HypK C-terminal region is responsible for high-affinity interaction with the C-terminal part of Naa15. In combination with acetylation assays, the HypK N-terminal region is identified as a negative regulator of the NatA acetylation activity. Our study provides mechanistic insights into the regulation of this pivotal protein modification.